A theory of plant function helps to explain leaf‐trait and productivity responses to elevation. Issue 5 (29th February 2020) - Peng, Yunke; Bloomfield, Keith J.; Prentice, Iain Colin
Summary: Several publications have examined leaf‐trait and carbon‐cycling shifts along an Amazon–Andes transect spanning 3.5 km in elevation and 16°C in mean annual temperature. Photosynthetic capacity was previously shown to increase as temperature declines with increasing elevation, counteracting enzyme‐kinetic effects. Primary production declines, nonetheless, due to decreasing light availability. We aimed to predict leaf‐trait and production gradients from first principles, using published data to test an emerging theory whereby photosynthetic traits and primary production depend on optimal acclimation and/or adaptation to environment. We re‐analysed published data for 210 species at 25 sites, fitting linear relationships to elevation for both predicted and observed photosynthetic traits and primary production. Declining leaf‐internal/ambient CO2 ratio ( χ ) and increasing carboxylation ( V cmax ) and electron‐transport ( J max ) capacities with increasing elevation were predicted. Increases in leaf nitrogen content with elevation were explained by increasing V cmax and leaf mass‐per‐area. Leaf and soil phosphorus covaried, but after controlling for elevation, no nutrient metric accounted for any additional variance in photosynthetic traits. Primary production was predicted to decline with elevation. This analysis unifies leaf and ecosystem observations in a common theoretical framework. The insensitivity of primary production to temperature is shown to emerge as a consequence of the optimisation of photosynthetic traits.